Plasma Exosomes at the Late Phase of Remote Ischemic Pre-conditioning Attenuate Myocardial Ischemia-Reperfusion Injury Through Transferring miR-126a-3p - Li, Danni; Zhao, Yang; Zhang, Chuyi; Wang, Fan; Zhou, Yan; Jin, Sanqing (Frontiers in Cardiovascular Medicine, 2021)
Background: Remote ischemic pre-conditioning (RIPC) alleviated the myocardial ischemia-reperfusion injury, yet the underlying mechanisms remain to be fully elucidated, especially at the late phase. Searching a key component as a transfer carrier may provide a novel insight into RIPC-mediated cardioprotection in the condition of myocardial ischemia-reperfusion. Objective: To investigate the cardioprotective effect of plasma exosomes at the late phase of RIPC and its potential signaling pathways involved. Methods and Results: Exosomes were isolated from the plasma of rats 48 h after the RIPC or control protocol. Although the total plasma exosomes level had no significant change at the late phase of RIPC (RIPC-exosome) compared with the control exosomes (Control-exosome), the RIPC-exosome afforded remarkable protection against myocardial ischemia-reperfusion (MI/R) injury in rats and hypoxia-reoxygenation (H/R) injury in cells. The miRNA array revealed significant enrichment of miR-126a-3p in RIPC-exosome. Importantly, both miR-126a-3p inhibitor and antagonist significantly blunted the cardioprotection of RIPC-exosome in H/R cells and MI/R rats, respectively, while miR-126a-3p mimic and agomir showed significant cardioprotection against H/R injury in cells and MI/R injury in rats. Mechanistically, RIPC-exosome, especially exosomal miR-126a-3p, activated the reperfusion injury salvage kinase (RISK) pathway by enhancing the phosphorylation of Akt and Erk1/2, and simultaneously inhibited Caspase-3 mediated apoptotic signaling. Conclusions: Our findings reveal a novel myocardial protective mechanism that plasma exosomes at the late phase of RIPC attenuate myocardial ischemia-reperfusion injury via exosomal miR-126a-3p.